##### Document information

Shadow Prices

**Economic interpretation?
**

*a x a x a x b
a x a x a x b
*

*a x a x a x b
x x x
*

*n n
*

*n n
*

*m m mn n m
*

*n
*

11 1 12 2 1 1

21 1 22 2 2 2

1 1 2 2

1 2 0

+ + + ≤ + + + ≤

+ + + ≤ ≥

. .. . ..

. .. .. . . .. .. .

. .. .. . . .. .. . . ..

, , .. .,

max
*x
*

*j j
j
*

*n
Z c x*= ∑

=1

Docsity.com

xj : units of activity j bi : resource level i aij : units of resource level i used per one unit

of activity j cj : return/loss from unit of activity j z : total return/loss z* : optimal return/loss

Docsity.com

what is the “value” of resource i ?

How much are we going to gain/lose if we have more from resource i ? Instead of bi we have bi + ε. As a result, instead of z* we now have z* +

∆. The value of ∆ generated by one unit of ε is

called the shadow price of resource i.
It is better to use the term “**marginal value
**

**of resource i**” ...... but ......
Docsity.com

Clue ... From duality theory we know that z* = y*b where y* is the optimal solution to the

dual problem. Furthermore, for problems in standard

form y* is equal to the reduced costs of the slack variables.

Docsity.com

More generally, y = cBB-1 is the “dual variable”, and for the last tableu, y

is an optimal solution for the dual.

Docsity.com

Recipe For problems in stadard form:

**The shadow price of the i-th resource is
equal to the optimal value of the i-th
dual variable.
**

Docsity.com

warning: The recipe “assumed” that the change in

the RHS value does not change the basis
itself, namely the elements of the basis are
assumed to be the same after the change.
**If this assumption is not valid, the recipe
**

**may not be valid.
**

Docsity.com

7.5.1 Complementary Slackness Theorem

*a x a x a x s b
a x a x a x s b
*

*a x a x a x s b
*

*x j n m
*

*n n
*

*n n
*

*m m mn n m m
*

*j
*

11 1 12 2 1 1 1

21 1 22 2 2 2 2

1 1 2 2

0 1

+ + + + =

+ + + + =

+ + + + =

≥ = +

.. . .. .

. .. .. . .. . . .. . ..

. .. .. . .. . . .. . .. . . .

, ,. . .,

max ... .. .
,*x s n n m
*

*Z c x c x s s s*= + + + + + +1 1 1 20 0

**Correction: Add si >= 0, i=1,2,...,m.
**Docsity.com

*a y a y a y t c
a y a y a y t c
*

*a y a y a y t c
y y y t t t
*

*m m
*

*m m
*

*n n mn m n n
*

*m n
*

11 1 21 2 1 1 1

12 1 22 2 2 2 2

1 1 2 2

1 2 1 2 0

+ + + − = + + + − =

+ + + − = ≥

. . . . ..

.. . . . . . . . . . . . . .

.. . . . . . . . . . . . . . . . .

, , . . . , , , , . . . ,

min . . . . . .
, *y t m m
*

*w b y b y t *= + + + + + 0tn 1 1 1 0

Docsity.com

Let (x,s) be a feasible solution to the primal and (y,t) be a feasible solution to the dual. Then a necessary and sufficient condition

for optimality of both solutions is sy = 0 ; tx = 0 Observe that because all the variables are non-

negative, this is equivalent to

Docsity.com

*s y i mi i *= =0 1 2, , , .. . ,

*t x j nj j *= =0 1 2, , , . . .,

Docsity.com

Example 7.5.2 In example 7.4.2 we have x = (12,0,0) ; s=(4,0) t = (0,4,14) ; y =(0,16)

Docsity.com

Clue ...

Eq. # *x*1 --- *xn s*1 --- *sm *RHS
--- --- --- (7.74)
Z *t*1 --- *tn y*1 --- *ym *yb

Docsity.com